(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The QT interval dispersion (QTd) was first developed as a measure of the variability in ventricular repolarization times over space. This study aimed for comparing Streptokinase vs primary PCI for ST-elevation myocardial infarction: a comparison of QTD before and after therapy. Methods: Two hundred patients who had a STEMI and were treated with streptokinase or primary PCI were included in this prospective observational trial. Two groups of identical size were created, one for patients who received fibrinolytic therapy and the other for those who underwent primary PCI. Reperfusion therapy was administered to all patients via primary PCI or fibrinolytics after a thorough history and physical examination, including a 12-lead electrocardiogram. Quantifying the QT interval and its variability. Results: The PCI group demonstrated significantly higher percent change of max QTD (P=0.001) and QTcD (P < 0.001). In patients with anterior or inferior infarctions, the median percent change of QTD was significantly higher in those who underwent PCI (-33%) than in those who underwent SK (-21.43%). Additionally, in patients with lateral or posterior infarctions, the median percent change of QTD was significantly higher in those who underwent PCI (-37.05%) than in those who underwent SK (-16.67%). Conclusion: QTD values were shown to decrease more in the primary PCI technique. This study demonstrated a greater reduction in the incidence of harmful arrhythmia after primary PCI was used to treat the arrhythmia, and an elevated QT interval is a risk factor for the development of such an arrhythmia.